Civil Legal Consequences of Asset Use Crypto as a Pawn Guarantee - Siregar, Dahris (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2026)
As specified in the Civil Code's Article 503, crypto assets as intangible commodities can be categorized as intangible objects. In addition, since crypto assets have economic value and can be traded, they can be used as collateral. Documents known as "proof of storing crypto assets" are provided by the depository management as evidence of ownership of cryptocurrency assets. The purpose of this research is to examine the characteristics of cryptocurrency assets as collateral and the legal ramifications of lien asset loss. Furthermore, what legal ramifications arise from employing cryptocurrency assets as security for a lien. This study approach combines secondary data from literature reviews with a kind of normative legal research. Furthermore, to analyse the data, qualitative analysis is employed. The findings indicated that the crypto asset feature can be used as collateral for a lien because the feature meets the lien requirements that protect the interests of creditors. One of these is inbezitstelling, which means that the mortgaged object is owned by the creditor.